GENE EXPRESSIONS IN THE INCIDENCE OF NON-SYNDROMIC CLEFT LIP AND PALATE - Al Hafiz, Al Hafiz; Supriyadi, Fauzia Latifah; Raymond, Benni (Transpublika Publisher, 2024)
The cleft lip and aisle (CL/P) are a craniofacial malformation caused by genetic mutations, environmental factors, or an interaction between the two. The development of the lip and auricle involves morphogenesis, molecular signaling pathways, mesenchymal-epithelial interactions, and auricle fusion. CL/P events involve initiation, growth, morphogenesis, and auctioning fusion. The Genome-Wide Association Study (GWAS) identified genes and loci associated with non-syndromic CL/P into 43 types significantly associated with single nucleotide polymorphism (SNP) near the gene. This systematic review aims to explore the genetic underpinnings of CL/P by analyzing findings from Genome-Wide Association Studies (GWAS) and identifying key genes and molecular pathways involved in palatogenesis. The most significant genes and loci in non-syndromic CL/P were Interferon regulatory factor 6 (IRF6), MAF bZIP transcription factor B (MAFB), Paired Box 7 (PAX7), Forkhead Box E1 (FOXE1), Msh Homeobox 1 (MSX1), T-box transcription factor 22 (TBX22), and Methylenetetrahydrofolate reductase (MTHFR). Genetic factors play an essential role in the pathogenesis of non-syndromic CL/P, including disruption of signaling pathways. IRF6, MAFB, PAX7, FOXE1, MSX1, TBX22, and MTHFR are genes that play a role in palatogenesis. Mutations in these genes have an impact on orofacial development.